Genotypic frequencies of the β-lactoglobulin, κ-casein and transferrin in Serbian Holstein-Friesian dairy cattle - Dragomir Lukač; Vitomir Vidović; Žolt Nemeš; Milanko Stupar; Anka Popović-Vranješ (Mljekarstvo)
The study included 765 Holstein cow for determining of β-lactoglobulin genotypes, 420 cows for determining κ-casein genotypes and 252 cows for determining transferrin genotypes, daughters of 18 sires. Among 765 cows, 172 were of the β-LG AA genotype, 448 were of genotype AB, and 145 were of BB genotype. The frequencies of genotypes AA, AB and BB were 0.23, 0.58 and 0.19, respectively. The frequency of alleles A and B, which was derived from the frequency of genotypes, was 0.52 for allele A and 0.48 for allele B. Among 420 cows, 105 were of the κ-casein AA genotype, 219 were of genotype AB, and 96 were of BB genotype. The frequencies of genotypes AA, AB and BB were 0.25, 0.52 and 0.23, respectively. The frequency of alleles A and B, which derived from the frequency of genotypes, was 0.51 for allele A and 0.49 for allele B. Among 249 cows, was identified 9 different genotypes of transferrin, 72 were of the Tf AD2 genotype, 50 were of genotype D1D2, 42 were of genotype D2D2, 28 were of genotype AD1, 20 were of genotype AA, 17 were of genotype D2E, 10 were of genotype AE and less than ten were of genotype D1D2 and D1E.The frequency of alleles A, D1, D2 and E, which was derived from the frequency of genotypes, was 0.30 for allele A, 0.19 for allele D1, 0.45 for allele D2 and 0.06 for allele E. In the studied population of Holstein Friesian dairy cattle in Serbia, a significant number of heterozygous individual and population variability were found. The large variability gives us the opportunity for further selection, favoring the genotype cows depending on the desired properties of milk (milk yield, content of milk fat and proteins) for further technological processing of milk. According to previous studies, it is obvious, that heterozygous cow tended to have a better production performance than the homozygous cows. This genetic information of polymorphic gene could be useful in marker assisted selection to improve production performance.